2017
DOI: 10.1186/s12879-016-2133-7
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and determinants of toxoplasmosis in pregnant women attending antenatal clinic at the university teaching hospital, Lusaka, Zambia

Abstract: BackgroundToxoplasmosis is a neglected zoonotic disease which is prevalent among pregnant women especially in Africa. This study aimed to determine the seroprevalence and determinants of the disease among pregnant women attending antenatal clinic at the University Teaching Hospital (UTH).MethodA cross-sectional study was employed where 411 pregnant women attending antenatal clinic at UTH were interviewed using closed ended questionnaires. Their blood was also tested for Toxoplasma gondii IgG and IgM antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
37
5

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 37 publications
12
37
5
Order By: Relevance
“…This result was higher compared to previous studies conducted among women with history of miscarriage in Mexico (38), but similar to spontaneous abortion rate in seropositive women for T. gondii infection reported in Pakistan (17%) (39), and lower than other studies done in Egypt (40), Iran (41), and India (42). When we linked the frequency of abortion to the presence of direct contact with cats, which was considered as a risk factor for having toxoplasmosis, the relationship was statistically significant (P. value = 0.031), similar to an association reported in Zambia (36).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This result was higher compared to previous studies conducted among women with history of miscarriage in Mexico (38), but similar to spontaneous abortion rate in seropositive women for T. gondii infection reported in Pakistan (17%) (39), and lower than other studies done in Egypt (40), Iran (41), and India (42). When we linked the frequency of abortion to the presence of direct contact with cats, which was considered as a risk factor for having toxoplasmosis, the relationship was statistically significant (P. value = 0.031), similar to an association reported in Zambia (36).…”
Section: Discussionsupporting
confidence: 74%
“…However, this seroprevalence of T. gondii antibodies was higher than that reported in European, North and West American continents (9, 34). Such variations could be due to different study settings in terms of multiple climatic conditions, heterogenous study population and risk factors profile such as contact with pets, hygienic practice, and feeding habit (28, 29, 31, 35, 36). The result of those who aged 21-30 years having the highest frequency of T. gondii infection (28.9%) was similar to previous reports (28, 29, 36) with the exception of one study conducted in Burkina Faso that showed these who aged more than 30 years were the most infected age group (35).…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal care (ANC) provides adequate measures against maternal-fetal transmission of several diseases, including toxoplasmosis and HIV [1,2]. Toxoplasmosis caused by Toxoplasma gondii is a neglected zoonotic disease and is asymptomatic [3,4]. Toxoplasmosis is prevalent worldwide whereby about one third to half of the global population is infected [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Infection with T. gondii has severe consequences in immune compromised hosts such as pregnant women, HIV patients and patients receiving chemotherapy or immunosuppressive drugs [4,5,9]. The prevalence of toxoplasmosis among pregnant women showed significant variation between continents and countries and ranges from 9 -92.5% [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation